Different quantitative measures of the impact of premature deaths on the community in Australia - Lawrence T. Lam (Elsevier, 2004)
Abstract Objective: Different quantitative measures based on the concept of years of potential life lost have been derived for assessing the burden of diseases and injuries. However, few studies have been conducted to compare the usefulness of these measures in terms of providing practical information. This study aims to examine the utility of different measures in assessing the impact of premature deaths on Australian society. Methods: This population‐based study was conducted utilising data on the underlying causes of death officially reported by the Australian Bureau of Statistics. The mortality rates, potential years of life lost (PYLL), potentially productive years of life lost (PPYLL), and the valued potential years of life lost (VPYLL), are calculated and compared for deaths due to all known underlying causes. Results: In comparison with other causes of death, injury deaths had the second‐highest annual rates of PYLL (1,206.7 years), the highest PPYLL (543.5 years), and VPYLL (489.7 years). Premature deaths due to injury were the only positively valued VPYLL among all major causes of death. Among injury deaths, intentional injury deaths caused the largest VPYLL (7,591.6 years), with a higher rate than unintentional injury deaths. Conclusion: As an indicator of the economic impact and burden of premature deaths to society, the VPYLL seems to be an advantageous utility. Injury poses the greatest public health problem to the Australian economy.